2019
DOI: 10.9734/ajee/2019/v9i430103
|View full text |Cite
|
Sign up to set email alerts
|

Industrialisation Scenario at Sreepur of Gazipur, Bangladesh and Physico-chemical Properties of Wastewater Discharged from Industries

Abstract: This study was conducted to explore the present trend and pattern of industrial growth with spatial distribution of industries and seasonal extent of physicochemical characteristics of wastewater at Sreepur of Gazipur, Bangladesh. The wastewater samples were collected from 5 locations in three seasons viz. pre-monsoon, monsoon and dry season. A total of 120 medium to large industries were surveyed, among those 52 were in red category, 53 were in orange-B category, 13 were in orange-A and only 2 were in green c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
11
1
Order By: Relevance
“…There is a progressive increase in industrial as well as urban wastes and effluents due to the rapid industrialization and urbanization. Such waste products and effluents are discharged into the rivers without any kinds of treatment, which have a significant contribution to the heavy metal content of river water and sediments [8][9][10][11][12][13]. These heavy metals and other toxic substances, which often lead to decrease in number of fish species in rivers and canals of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…There is a progressive increase in industrial as well as urban wastes and effluents due to the rapid industrialization and urbanization. Such waste products and effluents are discharged into the rivers without any kinds of treatment, which have a significant contribution to the heavy metal content of river water and sediments [8][9][10][11][12][13]. These heavy metals and other toxic substances, which often lead to decrease in number of fish species in rivers and canals of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason might be the vehicular movement and construction activities. The average Pb content in canal water of this study area during the monsoon season was 0.734 mg L 1 , which was beyond DoE recommended irrigation water quality limit (Hossain et al, 2019). Therefore, the value of Pb both in canal water and affected soil of the study area showed higher amounts of Pb in the monsoon season than the other two seasons.…”
Section: Lead (Pb)mentioning
confidence: 66%
“…A survey estimated a total of 120 medium to large industries in this area, among those 52 were in the red category, 53 were in the orange-B category, 13 were in the orange-A and only 2 were in the green category. Furthermore, among the surveyed industries about 33% didn't have any Effluent Treatment Plant (ETP) (Hossain et al, 2019). Thus, clean water containing canals being converted to the carrier of dark, filthy and foul smelled den.…”
Section: Introductionmentioning
confidence: 99%
“…A survey estimated a total of 120 medium to large industries in Sreepur of Gazipur area, among those 52 were in red category, 53 were in orange-B category, 13 were in orange-A and only 2 were in green category. Furthermore, among the surveyed industries about 33% didn't have any effluent treatment plant (ETP) [1]. The solid wastes are also used in land filling.…”
Section: Introductionmentioning
confidence: 99%